2022
DOI: 10.1007/s00213-022-06134-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of preexisting inhibitory control deficits vs. drug use history in mediating insensitivity to aversive consequences in a rat model of polysubstance use

Abstract: Rationale The nature and predictors of insensitivity to aversive consequences of heroin + cocaine polysubstance use are not well characterized. Objectives Translational methods incorporating a tightly controlled animal model of drug self-administration and measures of inhibitory control and avoidance behavior might be helpful for clarifying this issue. Methods The key approach for distinguishing potential contributions of pre-existing inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 89 publications
2
3
0
Order By: Relevance
“…Although there are conflicting studies concerning the predictive value of impulsivity and novelty-seeking on drug abuse, and how these traits are impacted by drug exposure, our findings align with previous studies [17,31,32] which show that both behavioral traits predict higher rates of cocaine intake, even though novelty-seeking can also result from drug use in low novelty-seekers. Unlike novelty-seeking, impulsivity was not affected following cocaine exposure, regardless of the baseline levels of impulsivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although there are conflicting studies concerning the predictive value of impulsivity and novelty-seeking on drug abuse, and how these traits are impacted by drug exposure, our findings align with previous studies [17,31,32] which show that both behavioral traits predict higher rates of cocaine intake, even though novelty-seeking can also result from drug use in low novelty-seekers. Unlike novelty-seeking, impulsivity was not affected following cocaine exposure, regardless of the baseline levels of impulsivity.…”
Section: Discussionsupporting
confidence: 90%
“…Studies performed in rodents to disambiguate whether impulsivity and novelty-seeking are causes or consequences of drug abuse have produced mixed results. Rats with high impulsivity, as identified by enhanced premature responding during behavioral inhibition tasks, exhibit increased rates of cocaine [16,17], nicotine [18], and alcohol [19] self-administration (SA), indicating that impulsive actions predics drug intake, although other studies failed to replicate this finding [20][21][22][23][24]. Moreover, the effect of drug exposure on impulsive action in rodents is unclear, with some studies showing either no alteration [25][26][27] or a worsening [24,[28][29][30] in impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, conditioning with opioid drugs (morphine or fentanyl) led to the formation of contextual reward memory and subsequent risk-taking behavior. These results resemble those from prior rodent studies using opioid self-administration punished by electrical footshocks, which reported near complete suppression of opioid seeking as a function of footshock intensity [6,7,[10][11][12][13][14][15]19]. However, similar studies have reported either incomplete suppression of opioid seeking or divergent behavioral responses that resulted in subgroups of either punishment-sensitive or punishment-resistant animals [8,9].…”
Section: Discussionsupporting
confidence: 83%
“…To investigate potential causality between opioid use and increased risky decision making, prior studies have attempted to model risky opioid use in laboratory animals. Results have shown that rodents will continue to seek opioids even when they must risk the threat of painful stimuli (e.g., electrical footshocks) to do so [6][7][8][9][10][11][12][13]. Other studies have made further attempts to model the use of opioids in a risky context by introducing an electrified barrier that animals had to cross to obtain the drug [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A widely-used procedure for demonstrating specificity of effect during drug self-administration sessions is to include a yoked control condition that passively receives either the psychoactive drug or saline ( Lecca et al, 2007 ; Mathieson et al, 2022 ). Generally, a yoked-saline design is used as a control when assessing for the pharmacological effects of nicotine and possible neuroadaptations elicited by the drug ( Palmatier et al, 2007 ; Gipson et al, 2013b ; Pittenger et al, 2018 ; Jin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%